Fruit quality of sweet cherry cultivars in superintensive orchards - Thurzó, Sándor; Szabó, Zoltán; Holb, Imre; Nagy, János; Farkas, Ervin; Drén, Gábor; Racskó, József; Dani, Mária; Nagy, Péter Tamás; Kincses, Sándorné; Veres, Zsuzsanna; Nyéki, József (Acta Agraria Debreceniensis, 2005)
The fruit quality of 15 sweet cherry cultivars (’Canada Giant’, ’Celeste’, ’Chelan’, ’Ferrovia’, ’Germersdorfi Rigle’, ’Katalin’, ’Karina’, ’Kordia’, ’Linda’, ’Regina’, ’Sam’, ’Sandra Rose’, ’Sunburst’, ’Sylvia’ and ’Techlovan’) was studied under super-intensive growing conditions at Nagykutas. We measured the fruit diameter, fruit width, fruit height, stem length and stem weight, fruit and pit weight and the total dry matter content. There were large differences among the cultivars. These differences are due to the genetic characteristics of fruits because all other conditions were the same. For 11 cultivars, we collected fruit samples several times /2-4/. We examined on this cultivars all the above listed fruit quality parameters. When examining these samples, we have gained information how earlier or later than optimal harvest time influences fruit quality.